2012
DOI: 10.1111/j.1474-9726.2012.00832.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin slows aging in mice

Abstract: Summary Rapamycin increases lifespan in mice, but whether this represents merely inhibition of lethal neoplastic diseases, or an overall slowing in multiple aspects of aging is currently unclear. We report here that many forms of age-dependent change, including alterations in heart, liver, adrenal glands, endometrium, and tendon, as well as age-dependent decline in spontaneous activity, occur more slowly in rapamycin-treated mice, suggesting strongly that rapamycin retards multiple aspects of aging in mice, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
500
1
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 589 publications
(540 citation statements)
references
References 31 publications
21
500
1
3
Order By: Relevance
“…A well‐known side effect of rapamycin treatment in humans and mice is testicular degeneration (Wilkinson et al ., 2012), and we observed that both the intermittent rapamycin and daily rapamycin treatment regimens significantly decreased testes mass (Fig. 3C).…”
Section: Resultsmentioning
confidence: 60%
“…A well‐known side effect of rapamycin treatment in humans and mice is testicular degeneration (Wilkinson et al ., 2012), and we observed that both the intermittent rapamycin and daily rapamycin treatment regimens significantly decreased testes mass (Fig. 3C).…”
Section: Resultsmentioning
confidence: 60%
“…In mice, rapamycin treatment increased testicular degeneration and cataract incidence (101) , and caused insulin resistance in some mouse strains. In a set of elegant studies, it was recently reported that the longevity effects of DR (via inhibition of mTORC1) can be uncoupled from the insulin-resistant effects (via inhibition of mTORC2 (89) ).…”
Section: Rapamycinmentioning
confidence: 99%
“…The inhibition of mTOR signaling with chronic, systemic 2.24-mg/kg (14 ppm) administration of rapamycin, a product of the soil bacteria Streptomyces hygroscopicus, extends life span in mice, even when introduced late in life (Harrison et al 2009). Rapamycin 4.7, 14, and 42 ppm in food also slows age-dependent pathology of the liver, heart, and tendons (Wilkinson et al 2012). A recent study demonstrated that chronic 2.24-mg/kg rapamycin inhibits age-associated cognitive decline (Halloran et al 2012).…”
Section: Introductionmentioning
confidence: 99%